Kepemmpinan Pendidikan Transformatif di SD Muhammadiyah Condong Catur - Setiawan, Farid; Hendrian, Hendrian; Wibowo, Joni Mukti; Athaillah, Rafi’ul Akmal; Rosdianti, Rosdianti (Lembaga Yasin AlSys, 2022)
This study aims to examine a transformational educational leadership system, especially in SD Muhammadiyah Condong Catur where by knowing how transformational educational leadership is, we will understand better if one day when we become a leader in a certain institution. Transformative leadership leadership model is a model pattern of leaders who have the power to influence their subordinates in certain ways. Subordinates feel very trust, loyal and respect towards their leader. Leaders really need to have the ability or expertise to take or determine actions to achieve the goals to be achieved together. This research method uses qualitative research methods, namely research methods based on literature by collecting various literature sourced from various journals, books, and various other sources to make it easier to conduct research on transformative educational leadership in schools in order to improve and develop teacher and student performance. After making references, then analyzing the collected data by reconstructing it so that it becomes a new concept by using content analysis that prioritizes the quality and validity of the data. This study uses the method of social rules in which there is a narrative in its presentation. Meanwhile, the evidence from the incident was taken from the field directly for observation so that the results were more accurate. Our research shows that transformational leadership from time to time has undergone very significant changes, especially in the current era of globalization.